CYP3A pharmacogenetics and tacrolimus disposition in adult heart transplant recipients. Issue 9 (11th July 2016) - Deininger, Kimberly M.; Vu, Anh; Page, Robert L.; Ambardekar, Amrut V.; Lindenfeld, JoAnn; Aquilante, Christina L.
Abstract: Background: Cytochrome P450 ( CYP ) 3A polymorphisms are associated with variable CYP3A metabolizing enzyme activity and tacrolimus pharmacokinetics. We sought to determine the singular and combined impact of CYP3A4*22 and CYP3A5*3 variants on tacrolimus drug disposition in adult heart transplant recipients. Methods: The retrospective study included 76 patients greater than one year post‐heart transplant and receiving tacrolimus. Patients were genotyped for CYP3A4*22 and CYP3A5*3, and combined genotypes were classified as follows: extensive metabolizers (EM, CYP3A4*1/*1 + CYP3A5*1 carriers), intermediate metabolizers (IM, CYP3A4*1/*1 + CYP3A5*3/*3, or CYP3A4*22 carriers+ CYP3A5*1 carriers), and poor metabolizers (PM, CYP3A4*22 carriers+ CYP3A5*3/*3 ). The primary outcome was tacrolimus dose‐adjusted trough concentration (C0 /D, ng/mL per mg/d). Results: In singular analysis, tacrolimus C0 /D did not differ significantly between CYP3A4*22 genotype groups. However, tacrolimus C0 /D was 1.8‐fold lower ( P <.001) in CYP3A5 expressers vs non‐expressers. When combined CYP3A genotypes were evaluated, tacrolimus C0 /D was 1.8‐fold lower in EMs vs IMs ( P <.001) and EMs vs PMs ( P =.001). Tacrolimus C0 /D did not differ significantly between CYP3A IMs vs PMs. Conclusion: Combined CYP3A genotype was associated with tacrolimus drug disposition in adult heart transplant recipients, but the effect was largely driven by CYP3A5*3 . These data suggest that CYP3A4*22 and combined CYP3A genotypes are unlikely to provide additional information beyond CYP3A5 genotype.